2001
DOI: 10.1021/jo010883s
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Intramolecular Radical Cyclizations of Acylsilanes in the Regiospecific Formation of Cyclic Silyl Enol Ethers

Abstract: Acylsilanes with terminal alpha-stannyl bromide or xanthate functionalities are prepared. Alpha-stannyl radicals generated from these acylsilanes undergo intramolecular cyclizations to give cyclic silyl enol ethers regiospecifically. The radical processes involve radical cyclization, Brook rearrangement, and beta-fragmentation in sequence. A tributylstannyl group serves as the radical leaving group. The newly formed sigma-bond and pi-bond are located between the same two carbon atoms. This approach is limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…For acylsilanes with terminal a-stannyl bromides 364, intramolecular radical cyclisation of a-stannyl radicals to acylsilanes led to the formation of fivemembered rings (Scheme 96). 9c, 154 Starting from a-bromoa-sulfonylacylsilanes 369, the radical cyclisation produced both five-and six-membered rings (Scheme 97). 154 In addition, Tsai and co-workers have investigated the intramolecular radical cyclisation of carbohydrate-based acylsilanes 374 to afford polyoxygenated carbocycles 375 (Scheme 98).…”
Section: Radical Reactions Involving Acylsilanesmentioning
confidence: 99%
“…For acylsilanes with terminal a-stannyl bromides 364, intramolecular radical cyclisation of a-stannyl radicals to acylsilanes led to the formation of fivemembered rings (Scheme 96). 9c, 154 Starting from a-bromoa-sulfonylacylsilanes 369, the radical cyclisation produced both five-and six-membered rings (Scheme 97). 154 In addition, Tsai and co-workers have investigated the intramolecular radical cyclisation of carbohydrate-based acylsilanes 374 to afford polyoxygenated carbocycles 375 (Scheme 98).…”
Section: Radical Reactions Involving Acylsilanesmentioning
confidence: 99%
“…The stereochemistry of 17 was determined by difference NOE experiments. Specifically, irradiation of H (2) in cyclopentanol 17a at d 3.94À3.99 (CDCl 3 ) resulted in a 16% enhancement of H(1) at d 4.26À4.37. On the contrary, irradiation of H(2) in 17b at d 3.75 only resulted in a 4% enhancement of H(1) at d 4.16À4.23.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 98%
“…2 As shown in Scheme 1, intramolecular radical cyclization of acylsilane 1 gives a cyclized alkoxy radical intermediate 2 with a silyl group attached at the b-position of the radical. A facile radical-Brook rearrangement 3,4 successfully drives the reaction toward the formation of a silyloxy-substituted radical 3.…”
Section: Introductionmentioning
confidence: 99%
“…1 For example, intramolecular radical cyclizations 2 with acylsilanes as the radical acceptors (Scheme 1) proved to be an useful method in the construction of five-and six-membered cyclic alcohols. 3 Several years ago we demonstrated that it was possible to construct silyloxy-substituted pyrrolizidinones, indolizidinones, and quinolizidinones via intra-molecular cyclizations of a-acylamino radicals 4 with acylsilanes (Scheme 1). 5 Polyhydroxylated alkaloids 6 (Scheme 2) represented by lentiginosine (1), 2-epi-lentiginosine (2), swainsonine (3), and castanospermine (4) can be potent and selective glycosidase inhibitors and may be useful as anti-cancer, anti-diabetic, and anti-viral agents, and immune stimulants.…”
Section: Introductionmentioning
confidence: 99%
“…3 Several years ago we demonstrated that it was possible to construct silyloxy-substituted pyrrolizidinones, indolizidinones, and quinolizidinones via intra-molecular cyclizations of a-acylamino radicals 4 with acylsilanes (Scheme 1). 5 Polyhydroxylated alkaloids 6 (Scheme 2) represented by lentiginosine (1), 2-epi-lentiginosine (2), swainsonine (3), and castanospermine (4) can be potent and selective glycosidase inhibitors and may be useful as anti-cancer, anti-diabetic, and anti-viral agents, and immune stimulants. 7 The biological potential of this class of compounds has triggered the development of many synthetic methods aiming at the synthesis of these natural products and their analogs.…”
Section: Introductionmentioning
confidence: 99%